Rabdomioma cardiaco biventricular. Reporte de un caso diagnosticado in utero por ecografía. Biventricular cardiac rhabdomyoma. Report of a case diagnosed in utero by echography. - Adis L. Peña Cedeño; Nancy Vasallo Pastor; Abel Faure Berty Pérez (ECIMED, 2001)
Se reporta el caso de un rabdomioma cardiaco congénito múltiple biventricular, diagnosticado a un feto in utero, mediante ultrasonido prenatal en una mujer de veinte años con un embarazo de 22 semanas. El seguimiento por ecografía fetal permitió la valoración del caso, procediéndose a la interrupción de la gestación y confirmación del diagnóstico. El estudio de la madre en la Consulta de Genética concluyó que era portadora de esclerosis tuberosa.The case of a congenital multiple biventricular cardiac rhabdomyoma diagnosed in a phetus in utero by prenatal ultrasound in a 20-year-old woman on the 22nd week of pregnancy is reported. The follow-up by fetal echography allowed to evaluate the case. Abortion was induced and the diagnosis was confirmed. The study of the mother at the Genetics Department concluded that she was carrier of tuberous sclerosis.